A patient with probable rare blood Group B(A) phenotype - Avineesh Chandra; P. M. Bala Bhasker; Romesh Jain; Rakesh Kumar; Subodh Srivastava (Asian Journal of Transfusion Science)
Karl Landsteiner discovered ABO blood group system in the early 20th century, but still, uncertainty remains in immunohematology while detection of ABO subgroups or weaker variants. The presence of weak subgroups in patient samples gives rise to the discrepancy in forward (cell) and reverse (serum) grouping. We here report a case of the B(A) phenotype in a patient who was diagnosed with chronic liver disease with acute pancreatitis, requiring packed red blood cells due to anemia. The blood group discrepancy was resolved using serological testing and adsorption–elution technique. Blood grouping by the tube technique showed 2+ agglutination with anti-A antisera, strong agglutination (4+) with anti-B, anti-AB, and anti-D antisera, 4+ agglutination with A1 cells, and no agglutination with B cells and O cells in serum grouping. Results for both eluate and last wash were negative to all the donor cells used. This report highlights the importance of cell and serum grouping, solving blood group discrepancy, and also in providing crossmatch compatible blood components without delay. This rare phenotype in a patient is the first of its kind reported from India.